Navigating Challenges in Community-based Research Aimed at Ending the HIV Epidemic Among Black Women - J. Richelle Joe; Shan-Estelle Brown; Andrea Dunn (Journal of Participatory Research Methods)
Our interdisciplinary team initiated a community-based participatory research project aimed at dismantling the gendered racism faced by Black women in healthcare settings that makes them vulnerable to HIV and other health conditions. During the data collection phase of the project, we encountered multiple challenges with the recruitment and enrollment of Black women in the study as well as with an influx of fraudulent responses that slowed down the research process. In this article, we discuss our research methodology followed by details of the challenges we faced and the processes we used to navigate those challenges.